Kontrol Diri dan Impulsive Buying pada Penggemar K-Pop di Komunitas X - Rijal Abdillah; Rifa Novia Ramadhani (Jurnal Psikologi, 2024)
ABSTRACT The spread of K-pop has influenced the personalities if its fans both positively and negatively. K-pop fans are known for negative stereotypes because they are considered excessive and impulsive in making purchases. There are several factors that influence impulsive buying, namely external factors and internal factors, wherein the internal factor is self-control. The purpose of this research was to find out the relationship between self-control and impulsive buying on K-pop fans in the X community. The method used in this study is a quantitative method with a correlational approach and a purposive sampling technique. This research instrument uses a self-control scale and impulsive buying scale. The results of a simple linear regression test show that the regression coefficient is -0.186 and the determinant coefficient value (R square) is 0.080 with a significance of 0.000 (p <0.05) which shows the effective contribution of the two variables is 8% and the rest is influenced by variables or factors others that were not examined in this study. The coefficient value shows a negative value, so it can be interpreted that self-control has a negative effect on impulsive buying. Keywords: Impulsive Buying, Self-control, K-Pop